Plankton Diversity in Tropical Wetlands Under Different Hydrological Conditions (Lake Tana, Ethiopia) - Kahsay, Abrehet; Lemmens, Pieter; Triest, Ludwig; De Meester, Luc; Kibret, Mulugeta; Verleyen, Elie; Adgo, Enyew; Wondie, Ayalew; Stiers, Iris (Frontiers in Environmental Science, 2022)
Plankton is an integral part of wetland biodiversity and plays a vital role in the functioning of wetlands. Diversity patterns of plankton in wetlands and factors structuring its community composition are poorly understood, albeit important for identifying areas for restoration and conservation. Here we investigate patterns in local and regional plankton richness and taxonomic and functional community composition in riverine papyrus swamps, river mouth wetlands, and lacustrine wetlands in the Lake Tana sub-basin, Ethiopia. Data on phytoplankton, zooplankton and environmental variables were collected from 12 wetlands during the dry and wet seasons of 2018. Redundancy analyses, and linear mixed effect models, were used to investigate differences in local environmental conditions and variation in plankton community richness and composition between wetland types. We also assessed the ecological uniqueness of the plankton community at each wetland by calculating the contribution of single-wetland (LCBD: comparative indicators of the ecological uniqueness of the wetland) and single taxon (SCBD) to overall variation in plankton community composition (Beta diversity, BDTotal). Beta regression models were used to investigate the relationships of LCBD and SCBD to environmental variables, wetland, and taxa characteristics. A total of 85 phytoplankton taxa, distributed among 18 Reynolds functional groups, and 57 zooplankton taxa were observed over the entire set of samples. Local plankton taxon richness was significantly higher in riverine papyrus swamps compared to river mouth wetlands. Several local environmental variables and the composition of the plankton community differed significantly between the three wetland types. The highest phytoplankton ecological uniqueness (LCBD) was detected in lacustrine wetlands, whereas the riverine papyrus swamps had the highest zooplankton ecological uniqueness. Based on our analyses, we recommend protecting the wetlands with high LCBD values and stress the importance of various wetland types for preserving the diverse plankton communities of Lake Tana wetlands.